Syntheses of Two 5-Hydroxymethyl-2′-DeoxyCytidine Phosphoramidites with TBDMS as the 5-hydroxyl protecting group and Their Incorporation into DNA - Dai, Qing (2011)
[Image: see text] 5-Hydroxymethylcytosine (5-hmC) is a newly discovered DNA base modification in mammalian genomic DNA that is proposed to be a major epigenetic mark. We report here the syntheses of two new versions of phosphoramidites III and IV from dU in 18 and 32% overall yields, respectively, with TBDMS as the 5-hydroxyl protecting group. Phosphoramidites III and IV allow efficient incorporation of 5-hmC into DNA and a “one-step” deprotection procedure to cleanly remove all the protecting groups. A “two-step” deprotection strategy is compatible with ultra-mild DNA synthesis, which enables the synthesis of 5hmC-containing DNA with additional modifications.